Implementasi Prinsip-Prinsip Sistem Manajemen Mutu ISO 9001:2008 di SMK Ekonomika Depok Jawa Barat - Hasyim Asy’ari; Zahruddin Zahruddin; Syipa Fauziah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
This study aims to describe the application of the principles of quality management system (SMM) ISO 9001:2008 in VOCATIONAL SCHOOL of economics. The method used in this research is descriptive qualitative approach. Data were collected using the documentation, interviews with principals, quality management representative (WMM), 2 teachers, and 3 students, and observation. The results show that the application of the principles of the ISO 9001:2008 at SMM SMK Economics Depok went well. This is evidenced by the existence of the school’s business that always maintains customers’ trust, a curriculum which is in accordance with the educational enhancement principles, the implementation of the planned program and goals, the involvement of the entire school’s members, continuous evaluation, problems resolution based on existing data and facts, and the mutual cooperation between the school and other parties. The results of this research is expected to be able to provide insight to the school’s principal to always foster a shared commitment to the various parties in the schools in regard to the implementation of the principles of the ISO SMM 9001:2008. Keywords: The quality of education, the principles of SMM 9001:2008, ISO quality management system (SMM)